(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This paper provides a legal analysis of students’ right to mental well-being in higher education, emphasizing institutional responsibilities amid escalating mental health crises. It explores whether universities hold legal duties under human rights conventions, tort law, negligence principles, and education statutes to safeguard student psychological health, beyond mere welfare provisions. Utilizing a qualitative doctrinal methodology, the study systematically reviews international and domestic legal frameworks, landmark case law, institutional policies, ethical guidelines, and implementation challenges. Key issues addressed include the evolving recognition of mental health as protected right, accountability deficits in resource allocation, conflicts between privacy and duty of care, and systemic gaps in policy enforcement. The central argument posits that higher education institutions bear a proactive legal obligation to mitigate foreseeable mental harm through comprehensive support systems, staff training, and transparent oversight. Ethical tensions and practical barriers are critiqued, revealing the need for reform. Recommendations advocate mandatory mental health policies, judicial precedents for accountability, and interdisciplinary policy integration to foster a rights-based institutional culture.